Pseudoaneurysm of the profunda femoris artery following hip surgery - Patel, Pratiksha Viral; Jayesh S. Patel,; Saurabh C. Parmar, (International Surgery Journal, 2023)
Pseudoaneurysm of the profunda femoris artery has been described as an iatrogenic phenomenon following orthopedic surgery. It may result due to trauma or direct arterial wall injury during dynamic hip screw fixation for proximal femur fracture. We present a case of a 65-year-old female who developed sudden pain and left thigh swelling one month after surgery for left sided intertrochanteric femur fracture. Computed tomography angiography of the left lower limb revealed the presence of a pseudoaneurysm in the upper left thigh. It was successfully treated with endovascular glue embolization followed by surgical excision of the pseudoaneurysm.